Design and Implementation of the Application Layer Communication Protocol based on Wireless Sensor Network - Changshun Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The user-defined communication protocol is the key step to develop application system based on Wireless Sensor Network. Through the analysis on the application of the wireless sensor network architecture and communication needs, a kind of simple and practical application layer communication protocol with detailed design of protocol data structure is proposed in this paper. Based on that, a communication protocol programming prototype is written in C# language. Through the test of wireless sensor network intelligent community monitoring system, it proves that the system data transmission based on this proposal is reliable and programming is simple and convenient. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3141